SP5.1.10 Quality of endoscopy reporting in newly diagnosed oesophageal cancers. (28th October 2021) - Cunningham, Danielle; Khan, Khurram; Gall, Lewis; Craig, Carol
Abstract: Aims: The gold standard for diagnosing oesophageal cancer is gastroscopy (OGD). It is essential that the index OGD report is of a high quality to enable effective communication and facilitate appropriate management decisions by the multidisciplinary team (MDT). This study aimed to analyse the quality of index OGD reports in patients with newly diagnosed oesophageal cancer. Methods: A retrospective cohort study of all newly diagnosed oesophageal cancers registered in a UK Regional Upper GI MDT between October 2019 and September 2020. The index OGD reports were assessed for documentation of 11 previously published quality indicators (QIs) (including proximal and distal margins, level and involvement of oesophago-gastric junction and presence of Barrett's) and compared by endoscopist grade and parent speciality. Results: A total of 243 new oesophageal cancers were diagnosed by 86 individual endoscopists. Mean patient age was 69.9 ± 11.2 years and 168 (69.1%) were male. 60 (24.7%) had impassable cancers. Overall, the median total QIs recorded for passable cancers were 7 (IQR 6-8). No report included all QIs. 30 (17.1%) reports were of "good quality" (≥9 QIs). Non consultant grade were more likely to record perfoming retroflexion (82.7 vs 69.0%, p = 0.039). Non surgeons were more likely to take photos (80.8 vs 64.5%, p = 0.015), document Barrett's (29.3 vs 11.8%, p = 0.006) and to record an overall greater number of QIs (median 8 vs 7, p = 0.011). Conclusions: Current endoscopy reporting standards of new oesophageal cancers are suboptimal. Further endoscopist education is required to highlight essential QIs and ensure good quality OGD reporting.